Improving Students’ Vocabulary Mastery through Word Association Strategy - Mohammad Iqbal; Hasna; Sukmawati Sadilia; Afrillia Anggreni (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study examined the effectiveness of the Word Association Strategy in improving the vocabulary mastery of eighth-grade students at SMP Negeri 4 Palu. Vocabulary learning in the classroom was dominated by conventional techniques that provided limited opportunities for students to develop meaningful word understanding and usage. To address this issue, the study employed a quantitative method using a quasi-experimental design with pre-test and post-test control groups. The population consisted of all eighth-grade students in the 2025/2026 academic year, from which two classes (VIII Cempedak and VIII Manggis) were selected through cluster random sampling. Class VIII Cempedak as the experimental group (n = 32) was taught using the Word Association Strategy, while Class VIII Manggis as the control group (n = 30) was taught using conventional methods. The study focused on students’ vocabulary mastery of word meaning and usage, particularly common nouns, action verbs, and descriptive adjectives. Data were collected through vocabulary tests and analyzed using descriptive statistics and an independent samples t-test at the 0.05 level of significance. The results showed that the experimental group’s mean score increased from 53.46 in the pre-test to 81.85 in the post-test, while the control group improved from 55.04 to 69.29. The t-test result revealed that the t-count (5.50) was higher than the t-table value (1.671), indicating a significant difference between the two groups. These findings demonstrate that the Word Association Strategy effectively enhances students’ vocabulary mastery by facilitating meaningful word connections. Practically, English teachers can incorporate structured word association activities into regular vocabulary instruction to promote deeper word retention and more active student engagement in junior high school classrooms.